Analysis of Sedimentation Rate In Peat Lakes : Case Study of Lake Teloko, South Sumatera - Awfa, Dion; Alfiradina, Cheisyha; Hanif, Muhammad Nashiruddin; Aziz, M. Ridwan Al; Rozzan, Farhan Baroo; Genisia, Miftahul Husna; Azizah, Rifka Noor (International Journal of Marine Engineering Innovation and Research, 2025)
Teloko Lake in Ogan Komering Ilir, South Sumatra, is a peat swamp ecosystem revitalized through dredging to increase water storage capacity and reduce flood risk. This study analyzed post-revitalization sedimentation, assessed water quality, and identified suspended particle characteristics to support lake management. Objectives included determining the distribution of Total Suspended Solids (TSS), sedimentation rates, and relationship between particle properties and hydrological conditions to assess revitalization impact. Sampling was located at five locations at depths of 0.68 to 1.30 meters during dry season in September 2025. TSS concentrations ranged between 681 and 740 mg/L, with an average of 710.92 mg/L and a standard deviation of ±9.6%, indicating uniformity across locations and no significant dredging impact. A 72-hour sedimentation test showed a very low settling rate, with particles remaining suspended without forming a clear sediment layer. This is due to the dominance of colloidal particles less than 20 µm, containing positively charged organic matter, creating repulsive forces that inhibit natural sedimentation. The results confirm natural peat water properties and lake activities have a stronger influence on sedimentation than technical revitalization. These findings support long-term conservation by recommending ecological approaches, such as natural coagulants, to maintain water storage capacity and preserve ecosystem function.